Candida zemplinina for Production of Wines with Less Alcohol and More Glycerol - Giaramida, P.; Ponticello, G.; Di Maio, S.; Squadrito, M.; Genna, G.; Barone, E.; Scacco, A.; Corona, O.; Amore, G.; di Stefano, R.; Oliva, D. (South African Journal of Enology and Viticulture, 2016)
We developed a new protocol for winery mixed fermentations, using the selected Candida zemplinina yeast strain Cz3. The results of a two-year study, in which red musts (Merlot in 2010; Merlot, Nero d’Avola and Frappato in 2011) were inoculated with Cz3, is discussed. These wines were compared with wines obtained by inoculation with commercial Saccharomyces cerevisiae yeast strains (NDA21 and AR06 in 2010; NDA21 in 2011), or with those obtained by spontaneous fermentation (only in 2011). The inoculation of Cz3 always resulted in a two-phase fermentation: the first phase was driven by the C. zemplinina strain, while the second was dominated by the indigenous S. cerevisiae yeasts coming from the grapes and/or the winery. In both years the Cz3 wines contained less alcohol and more glycerol than those made with the commercial yeast strains or those obtained by spontaneous fermentation. Triangle tests showed that a sensorial difference between wines could only be achieved through the utilisation of Cz3.